Pengaruh Kerja Sama Tim, Lingkungan Kerja, dan Motivasi Kerja Terhadap Kinerja Karyawan pada PT. Indofood CBP Sukses Makmur Tbk - Mila Syarmila syarmila syarmila (Universitas Mercu Buana, 2023)
This study was conducted with the aim of analyzing the Effect of Teamwork, Work Environment, and Work Motivation on Employee Performance at PT. Indofood CBP Sukses Makmur Tbk. The sample in this study was 40 employees of Indofood CBP Sukses Makmur Tbk. The data collection method uses survey methods, with the research instrument being a questionnaire. This study uses the Structural Equation Model-Partial Least Square (SEM-PLS) data analysis technique. The results of this study indicate that: (1) Teamwork has no effect on employee performance, (2) work environment has a positive effect on employee performance, (3) work motivation has no effect on employee performance at PT. Indofood CBP Sukses Makmur Tbk.